Single Mobile Micro Droplet-Particle Pairs Spatially Captured by Macro Host Droplets on a Superhydrophobic Surface - Gregory S. Watson; Bronwen W. Cribb; Jolanta A. Watson (Advances in Condensed Matter Physics)
In this preliminary study, we demonstrate how small single water droplets can be spatially captured on the surface of individual micron sized hydrophobic coated particles (C18) which adhere to the surface of a nonmobile larger host water droplet resting on a superhydrophobic surface. The formation of the larger droplet, particle adhesion to that droplet, and smaller droplet formation on the particle all take place spontaneously from condensation conditions. These micro droplet-particle pairs are confined to the surface (liquid-air interface) of the larger host droplet; however, they are free to engage with external forces to promote mobility. This response may find applications for particle pair transport on liquid surfaces. We also demonstrate that droplets can be captured or removed from the larger droplet surface via a self-propulsion mechanism.